Marianna (1565) de Lodovico Dolce ou le drame de la jalousie - Sandra Clerc (Etudes Epistémè)
The “tragic trend” that spread across Italy from the first decades of the sixteenth century was in full swing in the middle of the Cinquecento, when the genre left the circle of the Princes’ courts and the academies of men of letters to meet the powerful Venetian printing industry. Lodovico Dolce, who worked side by side with one of the main printers of the time, Gabriele Giolito, made a decisive contribution to the dissemination of ancient tragedies through the translation of works by Seneca, the rewriting of plays by Greek authors, and the composition of an original text, Marianna, published in 1565. This text takes up the formal characteristics that have now become traditional for Italian tragedy, while adapting the historical narrative to the new genre; at the same time, Marianna marks an important moment of transition in the broader concept of drama. The tragedy is, in fact, no longer just a work which serves as a didactic message addressed to the Prince, but becomes the means for discussing other fundamental contemporary questions: the power of feelings and the possibility to curb them, the conflicts between fidelity and morality, as well as the ability to endure adversity.